Guidelines for drinking-water quality (World Health Organization, 1997)
The guideline describes a “Framework for Drinking-water Safety” and discusses the roles and responsibilities of different stakeholders, including the complementary roles of national regulators, suppliers, communities and independent “surveillance” agencies